Red House (Govt. Buildings), Trinidad, B.W.I. - (:unkn) unknown (James Book Store, 2010)
Exterior view of government buildings located in Port of Spain, Trinidad. Postcard number 27.
Colour: Green, Brown and Blue; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Buildings--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; [1900]; Red House, The (Trinidad and Tobago); Parliament Building (Trinidad and Tobago)